2015
DOI: 10.1159/000433472
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Interleukin 12 Family Cytokines and Their Relevant Cytokines in Adult Patients with Chronic Immune Thrombocytopenia before and after High-Dose Dexamethasome Treatment

Abstract: Objective: We aimed to investigate the expression of interleukin 12 (IL-12) family cytokines (IL-12, IL-23, IL-27 and IL-35) and their relevant cytokines (IFN-γ, IL-4, IL-17A and IL-10) in patients with chronic immune thrombocytopenia (cITP) as well as the effect of high-dose dexamethasone (HD-DXM) treatment on this expression. Materials and Methods: DXM was administered orally at a dose of 40 mg per day for 4 consecutive days to 38 patients with cITP. We measured the plasma levels of IL-12p70, IL-23, IL-27, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Knowing this discrepancy regarding the importance of IL‐12 in endometriosis, we measured IL‐12 serum levels in endometriosis patients and healthy controls; however, we were unable to detect this cytokine in the serum samples. According to previous studies, serum levels of IL‐12 p70 varied from 1.5 to 2000 pg/ml in the control and different pathological conditions (Biswas et al., 2020; Li et al., 2015); therefore, we used an ELISA kit whose detection range was 4–500 pg/ml. We suggest using ELISA kits with higher sensitivity (0.1 pg/ml) might help to detect IL‐12 in the serum samples of controls or patients suffering from endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing this discrepancy regarding the importance of IL‐12 in endometriosis, we measured IL‐12 serum levels in endometriosis patients and healthy controls; however, we were unable to detect this cytokine in the serum samples. According to previous studies, serum levels of IL‐12 p70 varied from 1.5 to 2000 pg/ml in the control and different pathological conditions (Biswas et al., 2020; Li et al., 2015); therefore, we used an ELISA kit whose detection range was 4–500 pg/ml. We suggest using ELISA kits with higher sensitivity (0.1 pg/ml) might help to detect IL‐12 in the serum samples of controls or patients suffering from endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…An imbalance in Th1/Th2 cells and an increased proportion of Th17 cells were observed in patients with ITP, suggesting a role of T-cell dysfunction in ITP pathogenesis [14][15][16]. Several observational studies showed that HD-DXM treatment corrects the Th1-/Th2-chemokine imbalance [17], abnormal T-cell subsets [18], and serum cytokine expression imbalance in ITP [19,20]. Regulatory B-cells may play a role in ITP pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“… 60 After high-dose dexamethasone, the plasma levels of IL-12p70, IL-23, IL-27, IFN-γ and IL-17A were significantly decreased in patients with ITP compared with patients before high-dose dexamethasone treatment. 61 Conversely, the levels of IL-4, IL-10 and IL-35 in patients with ITP were considerably higher than those before treatment. 61 Similarly, intravenous immunoglobulin treatment corrects the peripheral deficiency of T reg cells, and increases IL-35 levels and platelet counts.…”
Section: Potential Relationship Between Il-35 and Itpmentioning
confidence: 90%
“… 61 Conversely, the levels of IL-4, IL-10 and IL-35 in patients with ITP were considerably higher than those before treatment. 61 Similarly, intravenous immunoglobulin treatment corrects the peripheral deficiency of T reg cells, and increases IL-35 levels and platelet counts. 62 These findings suggest that IL-35 levels might be used to evaluate the effectiveness of clinical treatment and predict disease severity.…”
Section: Potential Relationship Between Il-35 and Itpmentioning
confidence: 90%